Ictal lack of binding to brain parenchyma suggests integrity of the blood–brain barrier for 11C-dihydroergotamine during glyceryl trinitrate-induced migraine. (27th May 2016) - Schankin, Christoph J.; Maniyar, Farooq H.; Seo, Youngho; Kori, Shashidar; Eller, Michael; Chou, Denise E.; Blecha, Joseph; Murphy, Stephanie T.; Hawkins, Randall A.; Sprenger, Till; VanBrocklin, Henry F.; Goadsby, Peter J.
Abstract : See Dreier (doi: 10.1093/aww112 ) for a scientific commentary on this article. Breakdown of the blood–brain barrier has long been postulated to occur in migraine. Schankin et al. explore this possibility using PET with [ 11 C]-dihydroergotamine. The radioligand does not bind to the brain parenchyma at rest or during migraine attacks, suggesting that the blood–brain barrier remains intact during attacks. Abstract : Abstract : See Dreier (doi: 10.1093/aww112 ) for a scientific commentary on this article. For many decades a breakdown of the blood–brain barrier has been postulated to occur in migraine. Hypothetically this would facilitate access of medications, such as dihydroergotamine or triptans, to the brain despite physical properties otherwise restricting their entry. We studied the permeability of the blood–brain barrier in six migraineurs and six control subjects at rest and during acute glyceryl trinitrate-induced migraine attacks using positron emission tomography with the novel radioligand 11 C-dihydroergotamine, which is chemically identical to pharmacologically active dihydroergotamine. The influx rate constant Ki, average dynamic image and time activity curve were assessed using arterial blood sampling and served as measures for receptor binding and thus blood–brain barrier penetration. At rest, there was binding of 11 C-dihydroergotamine in the choroid plexus, pituitary gland, and venous sinuses as expected from the pharmacology of dihydroergotamine. However, there was no binding to the brain parenchyma, including the hippocampus, the area with the highest density of the highest-affinity dihydroergotamine receptors, and the raphe nuclei, a postulated brainstem site of action during migraine, suggesting that dihydroergotamine is not able to cross the blood–brain barrier. This binding pattern was identical in migraineurs during glyceryl trinitrate-induced migraine attacks as well as in matched control subjects. We conclude that 11 C-dihydroergotamine is unable to cross the blood–brain barrier interictally or ictally demonstrating that the blood–brain barrier remains tight for dihydroergotamine during acute glyceryl trinitrate-induced migraine attacks.